Annealing stability study of Co20Fe60B2020Fe60B20 perpendicular magnetic tunnel junctions. (2nd December 2016) - Chen, P J; Zhu, M; Tibus, S; Dyer, T; Piccirillo, J; Ocker, B; Shull, R D
Abstract: A full Co20 Fe60 B20 20 Fe60 B20 perpendicular magnetic tunnel junction (pMTJ) with (Co) multilayers as pinning layers and different functional multilayers stacks were made and annealed at different temperatures. The tunneling magnetoresistance ratio (TMR) and MgO barrier resistance-area (RA) product were measured and analyzed as a function of annealing temperature. The TMR of pMTJs dramatically declines with increasing annealing temperatures from 320 °C to 400 °C, while the RA increases with temperature from 375 °C to 450 °C. The pMTJs and partial stacks were also measured in a vibrating sample magnetometer (VSM). We found that the (Co) multilayers are very stable and maintain a magnetization direction perpendicular to the film plane up to 450 °C. However, the magnetization direction of the CoFeB above and below the MgO barrier rotates from perpendicular to in-plane with increasing annealing temperature. Furthermore, the CoFeB layer influences the adjacent (Co) layers to rotate at the same time. The pMTJs' elemental depth profiles in the as-deposited and annealed states were determined by secondary ion mass spectrometry (SIMS). We found that boron (B) and tantalum (Ta) migrate toward the top of the stack. The other elements (platinum (Pt), cobalt (Co), ruthenium (Ru), and magnesium (Mg)) are very stable and do not interdiffuse during annealing up to 450 °C.